Human activity recognition and tracking - Quak, June Ren Feng (2014)
As the population in Singapore grows older, the health-related problems trend will also be seen more commonly. As there will be an increasing number of elderly people with health-related problems likely to need assistant in daily living, the number of caretakers will soon be outnumbered. Therefore, it is necessary to build smart systems to aid the elderly people in their daily living environment.